2019
DOI: 10.1158/1078-0432.ccr-19-0032
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Correlates of Disease Progression and Treatment Response in Prospectively Characterized Gliomas

Abstract: Purpose: The genomic landscape of gliomas has been characterized and now contributes to disease classification, yet the relationship between molecular profile and disease progression and treatment response remain poorly understood. Experimental Design: We integrated prospective clinical sequencing of 1,004 primary and recurrent tumors from 923 glioma patients with clinical and treatment phenotypes. Results: Thirteen percent of glioma patients harbored a pathogenic germline variant, including a subset associate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(107 citation statements)
references
References 40 publications
1
106
0
Order By: Relevance
“…Other poor prognostic factors have also been reported, including a rapid growth rate of more than 8 mm/year and a poor initial performance status [27]. More recent studies have reported that homozygous loss of chromosome 9p21 with loss of CDKN2A, a common phenomenon in higher WHO grade gliomas, is also associated with a worse outcome in IDH-mutant astrocytomas and oligodendrogliomas [28][29][30].…”
Section: Epidemiology and Clinical Coursementioning
confidence: 99%
See 1 more Smart Citation
“…Other poor prognostic factors have also been reported, including a rapid growth rate of more than 8 mm/year and a poor initial performance status [27]. More recent studies have reported that homozygous loss of chromosome 9p21 with loss of CDKN2A, a common phenomenon in higher WHO grade gliomas, is also associated with a worse outcome in IDH-mutant astrocytomas and oligodendrogliomas [28][29][30].…”
Section: Epidemiology and Clinical Coursementioning
confidence: 99%
“…The immune checkpoint inhibitor avelumab, which targets the programmed death-ligand 1 (PD-L1) is being investigated in combination with hypofractionated radiation for patients with IDH-mutant gliomas that have transformed to grade IV following prior chemotherapy treatment (NCT02968940). A significant proportion of IDH-mutant gliomas that have previously been treated with alkylating chemotherapy develop a hypermutant phenotype [11,12,29], which could theoretically lead to increased neoantigen load in the tumor.…”
Section: Novel Perspectives In the Treatment Of Low-grade Gliomasmentioning
confidence: 99%
“…None of the cases found to have SMARCB1, CSF1R, SMAD4, and HRAS, mutations. Whereas when we searched in a glioma cohort of 1004 samples (https://www.cbioportal.org/MSKCC, Jonsson et al, 2019) on this portal cases found to have SMARCB1, CSF1R, SMAD4, and HRAS mutations are 1.3%, 1.4%, 0.6%, and 0.2% respectively.…”
Section: Commentmentioning
confidence: 99%
“…IDH1 and EGFR are most recurrently mutated cancer driver genes in GBM_TCGA dataset ( ). Poor prognostic markers included genetic changes in the EGFR mutations in this group ( 65 ), and among most driver genes, IDH mutations are good prognostic factor in diffuse gliomas ( 66 , 67 ).…”
Section: Discussionmentioning
confidence: 99%